Plasma brain-derived neurotrophic factor is higher after combat training (Randori) than incremental ramp test in elite judo athletes - Schor,B. (2019)
Elite judo demands high levels of physical and psychological skills. The brain-derived neurotrophic factor (BDNF) may be of particular interest in sports medicine for its ability to promote neuroplasticity. We investigated the plasma BDNF before and after a judo training session (Randori) and the maximal incremental ramp test (MIRT) in athletes from the Brazilian national judo team and compared the results between both exercise stimuli and sexes. Fifty-six elite judo athletes were recruited who performed each task on a separated day. Anthropometric, physiological, athletic parameters, and plasma BDNF levels were measured before and after the tasks (Randori and MIRT). The groups presented similar anthropometric and physiological characteristics at baseline for the two tasks. All athletes reached maximal performance for the tasks. Plasma levels of BDNF increased significantly after Randori and MIRT for all subjects, both men and women. When comparing both exercise stimuli, a greater increase in BDNF was observed after Randori. There was no significant difference in the delta BDNF between sexes. Our findings indicate that training specificity of sport gestures influenced the increase of blood BDNF levels.